2011
DOI: 10.1002/mds.23657
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular impairment and adaptive postural imbalance in parkinsonian patients with lateral trunk flexion

Abstract: Lateral trunk flexion is a very common clinical observation in patients affected by Parkinson's disease. Postural control is known to depend on vestibular, visual, and somatosensory information. The aim of this study was to investigate whether impairment of vestibular function can account for the postural alterations observed in parkinsonian patients with lateral trunk flexion. We evaluated vestibular function in 11 parkinsonian patients with lateral trunk flexion and in 11 age-, sex-, and disease duration-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 33 publications
4
87
2
2
Order By: Relevance
“…Previous studies have also shown reduced vestibular function in patients with PD [35], which was clinically characterised by vertigo, imbalance and/or falls.…”
Section: Page 14 Of 27mentioning
confidence: 90%
“…Previous studies have also shown reduced vestibular function in patients with PD [35], which was clinically characterised by vertigo, imbalance and/or falls.…”
Section: Page 14 Of 27mentioning
confidence: 90%
“…54 Impairment in vestibular function ipsilateral to the leaning side was found in all patients with Pisa syndrome. Interestingly, 4 of 11 patients without Pisa syndrome presented impairments in vestibular function, and two of them later developed ipsilateral Pisa syndrome.…”
Section: P I S a S Y N D R O M E I N P A R K I N S O N ' S D I S E A S Ementioning
confidence: 96%
“…Since the basal ganglia has a central role in the integration of the state of equilibrium to regulate motor commands appropriate to sensory experience, it is likely that this function cannot operate properly in patients with PD [19]. While vestibular dysfunction may play no or a minor role in PI in PD, many studies have supported the link between PI and the deficits in the proprioceptive function [17,[20][21][22]. On the other hand, the contribution of visual inputs is viewed as an adaptive strategy to compensate for the proprioceptive deficits [17].…”
Section: Introductionmentioning
confidence: 99%